Design Tables for Top- and Seat-Angle with Double Web-Angle Connections - Kim, Yosuk; Chen, Wai-Fah (Engineering Journal, 1998)
This paper provides a set of design tables, based on the AISC/LRFD Specification (1994), for the selection of top and seat-angle with double web-angle connections given beam sections and applied loads. These tables enable the engineer to rapidly select proper angle sizes and configurations as well as determine the moment-rotation curve for the connection. Design procedures and a comprehensive case study are also presented.